Evaluation of Environmental-Energy-Economy models used in the EU policy processes - Gibert Cruz, Helena (My University, 2010)
To assess energy policies and support decisions of policy makers, the development of models, which can simulate the future of emission-generating activities and their economic impacts, is currently a major field of interest. The aim of this work is to evaluate and scrutinize two reports from the European Council which have been used to assess climate policies and decide whether their possible projected scenarios are trustful and reliable. In order to prove the mentioned goal, it has been studied the features of the models used in the European Policy as PRIMES, POLES and the General Equilibrium Model for Energy-Economy-Environment (GEM-E3). Moreover, a detailed evaluation of the arguments underlying each of the overall results has been performed. Since there might not exist a single approach which can success to properly address all kind of issues, developers should help to better understand the application domain of a model and its limitations. Both reports may not be covering sufficiently those issues and since no sensitivity analyses have been performed through the results, using them for policy processes might be questionable.
Keywords: Teknik och social förändring; Technology and social change